Some questions of design of library and information technologies (Based on experience of universal scientific libraries) - Oglu, Ahmadov Elchin Yusif; Canpolad, Aliyeva Nurlana (Technium Social Sciences Journal, 2022)
The introduction of new technologies accelerates globalization and embraces new service areas. Trends in globalization in the national republics are closely monitored and studied, and concrete steps are being taken towards integration. Presenting national content and exploring national resources are important steps in the process of integration into global networks. Theoretical issues of designing library-information technologies were given in the material conference. At the same time, information was provided about the works carries out in the direction of designing library-information technologies in the world and in our country. Development perspectives of library-information technology design in the field of library activity optimization are discussed.